Two Uummarmiutun modals – including a brief comparison with Utkuhikšalingmiutut cognates - Berthelin, Signe Rix (Department of Linguistics, University of Toronto, 2017)
The paper is concerned with the meaning of two modal postbases in Uummarmiutun, hungnaq ‘probably’ and ȓukȓau ‘should’. Uummarmiutun is an Inuktut dialect spoken in the Western Arctic. The analyses are founded on knowledge shared by native speakers of Uummarmiutun. Their statements and elaborations are quoted throughout the paper to show how they have explained the meaning nuances of modal expressions in their language. The paper also includes a comparison with cognates in Utkuhikšalingmiutut, which belongs to the eastern part of the Western Canadian dialect group (Dorais, 2010). Using categories from Cognitive Functional Linguistics (Boye, 2005, 2012), the paper shows which meanings are covered by hungnaq and ȓukȓau. This allows us to discover subtle differences between the meanings of Uummarmiutun hungnaq and ȓukȓau and their Utkuhikšalingmiutut cognates respectively.